Correlation Of Cultural Beliefs and Chronic Energy Deficiency During Pregnancy with Stunting in Children Aged 0-24 Months in Jatipurno, Wonogiri - Dewi, Annisa Puspa; Shabrina, Amalina; Aryoseto, Lukman (Faculty of Medicine Universitas Sebelas Maret, 2024)
Introduction: Stunting is a multifactorial issue that results in impaired growth and development in children. Maternal nutritional history, especially Chronic Energy Deficiency (CED), has an impact on child stunting. Infants with low birth weight are more likely to be stunted if their mothers have CED. The high rate of stunting in Jatipurno, Wonogiri is also influenced by culture beliefs in local community, which includes early supplemental feeding, dietary restrictions for pregnant mothers, and a high birth rate. This study aimed to see the correlation between CED during pregnancy and cultural beliefs (early complementary feeding, maternal food restrictions during pregnancy, and number of children) with stunting in children aged 0-24 months.Methods: This was an observational study with a retrospective case control approach. Purposive sampling based on the inclusion and exclusion criteria was used in this study. Subjects were children aged 0-24 months in Jatipurno, Wonogiri with normal and stunted nutritional status. Stunted children were allocated into case group (n=16) and normal children were allocated into control group (n=16). Statistical analysis performed with chi-square and multiple logistic regression using SPSS.Results: There was a significant relationship between CED during pregnancy with the incidence of stunting in children aged 0-24 months in the Jatipurno Health Center Working Area, with a p value of 0.008 (p<0.05) and OR value of 27.323.Conclusion: CED during pregnancy was a significant risk factor for stunting in children aged 0-24 months in Jatipurno, Wonogiri. There was no significant correlation between cultural beliefs (early complementary feeding, maternal food restrictions during pregnancy, and number of children) with stunting in children aged 0-24 months.